(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The hospitality industry is an innovative and very competitive one. The students can also specialize in other areas of the industry, from guest services to events planning and culinary services. Every year, baking evolves and innovates, and it has its trends, like new flavors, new styles, and ways of making it. Hospitality management students encountered problems in enhancing their baking skills and gaining knowledge using the bread and pastry laboratory, and this study wants to help in adjusting time and renovating the laboratories for the benefit of the students and school administration. The findings show that students are highly beneficial in having entrepreneurial, enhancing their creativity, teamwork, and problem-solving skills in the workplace, and also in developing their technical skills. The results also show that the bread and pastry laboratory is functional for students to use when practicing their baking skills. There are factors that can affect learning enhancement in practicing baking skills of the students in the bread and pastry laboratory, and this study can help to make adjustments of time and renovate the laboratories for the future students of Bestlink College of the Philippines. The researchers came out with the recommendation that professional teachers of the BSHM must always be hands-on in guiding and be attentive to the development of the students’ baking skills. The school administration should adjust the time allotted to the students in every laboratory simulation and in practicing their baking skills. The researchers also recommend that the school administration renovate the bread and pastry laboratory to make more space for students who are using the laboratory and provide more storage lockers for student bags and other personal belongings. Students must know the importance of being responsible in the maintenance of the tools and equipment while using them in laboratories for future students of BSHM.